2015
DOI: 10.1016/j.celrep.2015.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA Ceruloplasmin Promotes Cancer Growth by Altering Glycolysis

Abstract: SUMMARY Long noncoding RNAs (lncRNAs) significantly influence the development and regulation of genome expression in cells. Here, we demonstrate the role of lncRNA ceruloplasmin (NRCP) in cancer metabolism and elucidate functional effects leading to increased tumor progression. NRCP was highly upregulated in ovarian tumors and knockdown of NRCP resulted in significantly increased apoptosis, decreased cell proliferation, and decreased glycolysis compared with control cancer cells. In an orthotopic mouse model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 30 publications
1
83
0
Order By: Relevance
“…It has been shown to be significantly up-regulated in ovarian tumors [28] . Unlike control cancer cells, the knockdown of NRCP increased apoptosis, decreased cell proliferation, decreased glycolysis, and reduced migration.…”
Section: Non-coding Rna Ceruloplasmin (Nrcp)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to be significantly up-regulated in ovarian tumors [28] . Unlike control cancer cells, the knockdown of NRCP increased apoptosis, decreased cell proliferation, decreased glycolysis, and reduced migration.…”
Section: Non-coding Rna Ceruloplasmin (Nrcp)mentioning
confidence: 99%
“…Unlike control cancer cells, the knockdown of NRCP increased apoptosis, decreased cell proliferation, decreased glycolysis, and reduced migration. In addition, siRNA-mediated silencing of NRCP has reduced tumor growth in an orthotopic mouse model of ovarian cancer [28] .…”
Section: Non-coding Rna Ceruloplasmin (Nrcp)mentioning
confidence: 99%
“…However, the role of lncRNAs in mediating BCBM is still unclear. Targeting of lncRNAs using locked nucleic acids or a siRNA-based strategy has been successfully applied in several preclinical models (12,14). Here, we report that elevated expression of an lncRNA we refer to as Lnc-BM (long noncoding for brain metastasis) in primary breast cancer exhibits higher rates of recurrence to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, some studies have reported that lncRNAs can regulate carbohydrate metabolism progression in cancers. For instance, lncRNA GCASPC regulate glycolysis in cancer cells by directly binding with key glycolytic enzymes [30] and lncRNA NRCP is an intermediate binding partner between STAT1 and RNA polymerase II, leading to increased expression of glucose-6-phosphate isomerase [31]. Zhao et al reported that LINC00092 interacts with 6-phosphofructo-2-kinase/fructose-2, 6-biphosphatase 2 (PFKFB2) and is involved in increased glycolysis levels in ovarian cancer metastasis [32].…”
Section: Discussionmentioning
confidence: 99%